Service Innnovation, Service Delivery System, and Customers’ Satisfactory’s Correlation with Official Honda’s Dealer’s Customers’ Loyalty - Jati, L. Jatmiko; Nuryakin, Nuryakin; Handayani, Siti Dyah (Interdisciplinary Social Studies, 2022)
Background: Consumers will be more picky in choosing services and products as a result of the tight competition and the decline in consumer spending power caused by the Covid-19 pandemic factor. Consumers will opt for high-quality services or products at reasonable costs, as well as the greatest service and promotions that can entice them. As a result, organizations must carefully assess the four areas in order to meet consumer expectations. Aim: This study aims to examine the effect of service innovation, service delivery system, and customer satisfaction on customer loyalty at Honda authorized dealers. Method: This study uses a quantitative research approach to investigate the relationship between service innovation, service delivery systems, customer satisfaction, and customer loyalty. To achieve the research objectives, data were collected from respondents, namely consumers of authorized Honda dealers in Bantul Regency. Using structural equation modeling, and after a series of exploratory and confirmatory factors were analyzed, the authors tested an integrated model of the relationship between service innovation, service delivery systems, customer satisfaction, and customer loyalty. Findings: The results of this study indicate that service innovation has a significant effect on service delivery systems, service innovations have a significant effect on customer satisfaction, service delivery systems have a significant effect on customer satisfaction, service innovations have an insignificant effect on customer loyalty, service delivery systems have an insignificant effect on customer loyalty, and customer satisfaction has a significant effect on customer loyalty.